Kallikrein immobilized on magnetic beads for activity-based assays using mass spectrometry - Rocha, Camila Loreta; Cardoso, Carmen Lúcia (Frontiers in Analytical Science, 2025)
A crucial step in drug discovery involves identifying active molecules, which depends on fast and efficient screening assay methods. Kallikreins a family of serine protease enzymes, play a pivotal role in biological fluids and tissues. Deregulated activity and expression of human KLKs have been implicated in various pathologies, so these enzymes constitute attractive biological targets for discovering molecules that can modulate their activity. The novelty of the present study is the IMER-pKLK-MB bioreactor resulting from immobilization of porcine pancreas kallikrein (pKLK) on magnetic beads which proved highly active and stable. For example, over 60% of IMER-pKLK-MB activity was maintained after it was incubated in 70% methanol. In addition, even after being stored for 11 months, IMER-pKLK-MB allowed for at least 10 consecutive cycles of activity, which attested to its excellent stability. Parameters such as KMapp and IC50 for leupeptin confirmed that the immobilized pKLK retained its ability to recognize both the substrate and reference inhibitor. We optimized an off-flow assay based on high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS) and IMER-pKLK-MB to evaluate the inhibitory activity of some molecules toward pKLK. We also evaluated the kinetic parameter (KMapp = 81.2 ± 18 μmol.L−1) and qualified the method by using leupeptin as standard inhibitor (IC50 = 2.15 ± 0.4 μmol.L−1). The developed and qualified method proved an important and reliable approach for screening ligands and can be used to screen KLK inhibitors.